2010
DOI: 10.26719/2010.16.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasound, clinical and maternal estimates of birth weight in term women

Abstract: Accurate prenatal estimation of birth weight is useful in the management of labour and delivery. This study compared the accuracy of ultrasound, clinical and maternal estimates of fetal weight in 246 parous women with singleton, term pregnancies admitted for scheduled caesarean section. The sensitivity and specificity of predicting birth weight by ultrasound measures were 12.6% and 92.1%, by clinical palpation were 11.8% and 99.6% and by maternal estimate were 6.3% and 98.0% respectively. Clinicians' estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…They concluded that abdominal palpation and Johnson's technique 7 can be used as alternatives to ultrasound for estimation of fetal weight, particularly if the measurements are taken by experienced, skilled person. 18 It was found that mean weight by Dawn's was 2.86 kg which is comparable to mean birth weight.…”
Section: Discussionmentioning
confidence: 51%
“…They concluded that abdominal palpation and Johnson's technique 7 can be used as alternatives to ultrasound for estimation of fetal weight, particularly if the measurements are taken by experienced, skilled person. 18 It was found that mean weight by Dawn's was 2.86 kg which is comparable to mean birth weight.…”
Section: Discussionmentioning
confidence: 51%
“…3 In one study done in Nigeria showed that clinical estimation of birth weight is as accurate as routine ultrasonographic estimation except in low birth weight babies. Therefore, when the clinical method suggests weight smaller than 2500 g, subsequent sonographic estimation is recommended to wield a better prediction and to further evaluation fetal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Correct EFW values are also important when intrauterine growth is restricted and in preterm labour. 3 The present study was undertaken to determine the accuracy of birth weight estimation by routine antepartum sonography at term.…”
Section: Introductionmentioning
confidence: 99%
“…(a) clinical techniques based on abdominal palpation of foetal parts and calculations based on fundal height and (b) sonographic measures of skeletal foetal parts [4][5][6] . Ultrasound estimation of fetal weight, while being accurate to a degree, is associated with error ranging from ±6 to 11% depending on parameters measured and the 7 .…”
Section: Introductionmentioning
confidence: 99%